New treatments to disinfect vine cuttings with Phaeomoniella chlamydospora and the reason for the control - Brambatti, Fabiana; Leite, Luís Garrigós; Padovani, Carlos Roberto [UNESP]; Bueno, César Júnior (Instituto Biológico, 2023)
Petri disease is a problem for vineyard caused mainly by the fungus Phaeomoniella chlamydospora. Contaminated seedlings are source of inoculum for the disease. Treatment to disinfect vine rootstock cuttings for seedling production is hot water treatment (HWT) by 50 °C for 30 min, but the efficiency is contested. To improve its efficacy, the study aimed to assess the combination of the following methods and the reason for the control: i) exposition of the fungus to five different temperatures in HWT bath for 30 min; ii and iii) exposition of the fungus and also plants infected with P. chlamydospora to different disinfection treatments (biofumigation = soil + cabbage at 40 °C; temperatures of 40 and 23 °C, all in microcosm), in different periods (7, 14 and 21 days), with and without additional HWT (51 °C for 30 min). The results showed that HWT with high temperatures (55–70 °C) for 30 min inactivated the fungus. Biofumigation technique at 40 °C and the temperature solely of 40 °C applied for up to 21 days and combined with HWT (51 °C for 30 min) inhibited mycelial growth and inactivated the fungus in vine plant tissues without compromising the rooting.
Keywords: Petri disease; soilborne fungus, seedlings; alternative control; grapevine